Відображення класів UML до дескриптивної логіки для семантичного моделювання об’єктів - Новицький, Олександр (Видавництво Львівської політехніки, 2016)
In the article, propose mapping from UML class diagrams to SHOIQ of descriptive logic. Made approach through extension the UML notations by using stereotypes as close to semantic structures. Specified on the causes and problems that arise in such mapping.
Keywords: UML; дескриптивна логіка; семантичний веб; валідація діаграм класів UML